The holy cities of Arabia - Rutter, Eldon, 1894-1956? (London)
xiii, 574 s.
Keywords: "FEW BRITISH EXPLORERS IN ARABIA have produced books whose importance as travelogues is trans-cended by their literary quality. One such is The Holy Cities of Arabia, published to critical acclaim in 1928, with its author hailed as a worthy successor to Burckhardt, Burton and Doughty. Unrivalled among works by Western travellers to Islam s holy cities, this account of a pilgrimage to Makkah in 1925 26 is made all the more remark-able by its author s timing. In 1925 Abd al- Aziz Ibn Saud brought to an end centuries of rule over the Hijaz by the Hashimite sharifs and their Ottoman overlords. Rutter, living as a learned Muslim Arab in a Makkan household, had a ringside seat as Riyadh imposed its writ on Islam s holy cities. As striking as his account of life in Makkah before modernization are his interviews with Ibn Saud, and his journeys to al-Ta if and to the City of the Prophet, al-Madinah. The Holy Cities of Arabia proved to be its author s only full-length work. After a brief career as a Middle East traveller, Rutter lapsed into obscurity. This new edition aims to revive a neglected masterpiece and to establish Rutter s reputation. Little was known about him until now and the introduction tells the story of his life for the first time, assessing his talents as a travel writer and analysing his significance as a British convert to Islam." --